THE CORRELATION BETWEEN STUDENTS' ANXIETY LEVEL AND STUDENTS' GPA SCORE - Fitri Wulandari Paklang (fsip.teknokrat.ac.id, 2022)
GPA or Grade Point Average is the accumulation of the final score of all the scores obtained by students during college. There are many students who feel anxious when they will receive a study result card. This study aims to find out about the causes of student anxiety when receiving the study results card while they are studying, with this study aims to find solutions on how to eliminate or reduce student anxiety about the GPA they obtained. The method used for this research is quantitative data collection. The data was collected using a questionnaire which will be distributed to students using google form. The respondents of this study are the students of English Education students at UniversitasTeknokrat Indonesia. So it is hoped that this research can run smoothly and well.